Clinic Predictive Factors for Insufficient Myocardial Reperfusion in ST-Segment Elevation Myocardial Infarction Patients Treated with Selective Aspiration Thrombectomy during Primary Percutaneous Coronary Intervention. (7th November 2016) - Tian, Jinfan; Liu, Yue; Song, Xiantao; Zhang, Min; Xu, Feng; Yuan, Fei; Lyu, Shuzheng
Abstract : Background . Insufficient data are available on the potential benefit of selective aspiration and clinical predictors for no-reflow in STEMI patients undergoing primary percutaneous coronary intervention (PPCI) adjunct with aspiration thrombectomy. Objective . The aim of our study was to investigate clinical predictors for insufficient reperfusion in patients with high thrombus burden treated with PPCI and manual aspiration thrombectomy. Methods . From January 2011 till December 2015, 277 STEMI patients undergoing manual aspiration thrombectomy and PPCI were selected and 202 patients with a Thrombolysis in Myocardial Infarction (TIMI) thrombus grade 4~5 were eventually involved in our study. According to a cTFC value, patients were divided into Group I (cTFC > 40), namely, insufficient reperfusion group; Group II (cTFC ≤ 40), namely, sufficient reperfusion group. Results . Univariate analysis showed that hypertension, multivessel disease, time from symptom to PCI (≧4.8 hours), and postaspiration cTFC > 40 were negative predictors for insufficient reperfusion. After multivariate adjustment, age ≧ 60 years, hypertension, time from symptom to PCI (≧4.8 hours), and postaspiration cTFC > 40 were independently associated with insufficient reperfusion in STEMI patients treated with manual aspiration thrombectomy. Upfront intracoronary GP IIb/IIIa inhibitor (Tirofiban) was positively associated with improved myocardial reperfusion. Conclusion . Fully identifying risk factors will help to improve the effectiveness of selective thrombus aspiration.